Size-Dependent Fullerenes for Enhanced Interaction of l-Leucine A Combined DFT and MD Simulations Approach - Jana, Sourav Kanti (Langmuir : the ACS journal of surfaces and colloids, 2024)
Fullerene-based biosensors have received great attention due to their unique electronic properties that allow them to transduce electrical signals by accepting electrons from amino acids. Babies with MSUD (maple syrup urine disease) are unable to break down amino acids such as l-leucine, and excess levels of the l-leucine are harmful. Therefore, sensing of l-leucine is foremost required. We aim to investigate the interaction tendencies of size-variable fullerenes (CX; X = 24, 36, 50, and 70) toward l-leucine (LEU) using density functional theory (DFT-D3) and classical molecular dynamics (MD) simulation. The C24 fullerene shows the highest affinity of the LEU biomolecule in the gas phase. Smaller fullerenes (C24 and C36) show stronger interactions with leucine due to their higher curvature in water environments. Moreover, recovery times in the ranges of 1010 and 104 s make it a viable candidate for the isolation application of LEU from the biological system. Further, the interaction between LEU and fullerenes is in line with the natural bond order (NBO) analysis, Mulliken charge analysis, quantum theory atom in molecule (QTAIM) analysis, and reduced density gradient (RDG) analysis. At 310 K, employing the explicit water model in classical MD simulations, fullerenes C24 and C36 demonstrate notably elevated binding free energies (-24.946 kJ/mol) in relation to LEU, showcasing their potential as sensors for l-leucine. Here, we demonstrate that the smaller fullerene exhibits a higher potential for l-leucine sensors than the larger fullerene